Investigation into the Optical and Physical Features of ZnO Nanoparticles Produced on Different Substrates - Jony, Siluval Raju Mary; Muruganantham, Subramanian; Kumar, Ravinder; Shanmugan, Sengotaiyan (Current Nanoscience, 2026)
IntroductionThis study aimed to investigate the structural alterations of nanoparticles due to external forces. These forces, both direct and indirect, are crucial in changing the structures and characteristics of nanoparticles, which may have an impact on important variables and results.MethodsThe main focus of this study was on how researchers might modify the characteristics of nanoparticles by using a simple technique and adding precursor chemicals. The employed methodology, referred to as the simple bath method, made it easier to prepare and characterize composite nanoparticles using high-resolution TEM, XRD, SEM, and UV. To obtain important information, a comparative examination was carried out against standard market combinations.ResultsThis study explored the size and shape fluctuations of nanoparticles as identified by XRD and SEM investigations. Using Tauc plots for UV-vis spectroscopy, the refractive indices of the nanoparticles were calculated, and energy gaps, extinction coefficients, and dielectric constants were visualized. Moreover, ZnO nanoparticles were tested against Gram-positive (S pneumonia, Bacillus subtilis, and Bacillus megaterium) and Gram-negative (Klebsiella pneumonia, Shigella dysenteriae, ‘E-coli’) bacteria using an agar well diffusion process. Region reserve values (mm) were measured after twenty-four hours at thirty-seven degrees Celsius.ConclusionThe common antibiotic amoxicillin (10 µg/disc) was used as a standard. The activity of IN, ISB, ISC, and ISN on bacteria and fungi was examined. It was found that ZnO nanoparticles exhibited antibacterial capabilities, such as ion release and rupture, as well as the generation of antibacterial properties of IN, ISB, ISC, and ISN. IN, where ZnO nanoparticles alone were evaluated directly to establish baseline activity; ISB, where Lawsonia inermis (henna) extract was combined with ZnO nanoparticles in a Petri dish under different substrates and conditions; ISC, where Lawsonia inermis extract with ZnO nanoparticles was combined in a concave dish and tested under varying substrates and conditions; and ISN, where Lawsonia inermis extract with ZnO nanoparticles was further doped with NaOH.
Keywords: TEM